2007
DOI: 10.1002/cncr.22724
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking and the use of noncigarette tobacco products in association with risk for pancreatic cancer: A case‐control study

Abstract: In this work, we demonstrate the possibility to modify the electric‐field distribution of a radio frequency (RF) coil to generate electric field‐free zones in the body without significantly altering the transmit sensitivity. Because implant heating is directly related to the electric‐field distribution, implant‐friendly RF transmit coils can be obtained by this approach. We propose a linear birdcage transmit coil with a zero electric‐field plane as an example of such implant‐friendly coils. When the zero elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 36 publications
4
51
1
2
Order By: Relevance
“…An approximately twofold increased risk for pancreatic cancer was observed among ever smokers compared with non-smokers (Fuchs et al, 1996;Muscat et al, 1997;Hassan et al, 2007). Smoking is also a major risk factor of lung, oesophagus and kidney cancers (Chiu et al, 2001;Ghaneh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An approximately twofold increased risk for pancreatic cancer was observed among ever smokers compared with non-smokers (Fuchs et al, 1996;Muscat et al, 1997;Hassan et al, 2007). Smoking is also a major risk factor of lung, oesophagus and kidney cancers (Chiu et al, 2001;Ghaneh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of tobacco smokers from such studies is important to estimate the independent effect of passive smoking. Thus far, four case-control (14)(15)(16)(17) and four cohort studies (7,9,18,19) have examined the relationship between passive smoking exposure and the risk of pancreatic cancer. Three of these studies observed a positive association with passive smoking in never smokers (7,15,18).…”
Section: Introductionmentioning
confidence: 99%
“…pdf) and three case-control (Villeneuve et al, 2004;Hassan et al, 2007;Lo et al, 2007; the former two studies are summarized in Table 2.18 available at http://monographs.iarc.fr/ENG/ Monographs/vol100E/100E-02-Table2.18.pdf).…”
Section: Cancer Of the Pancreasmentioning
confidence: 99%
“…Data from the majority of the studies (Nishino et al, 2001;Villeneuve et al, 2004;Gallicchio et al, 2006;Hassan et al, 2007;Bao et al, 2009) suggested lack of an association of cancer of the pancreas with never smokers exposed to secondhand tobacco smoke in adulthood at home or at work. (RR 1.2 (95%CI: 0.45-3.1) and 1.21 (95%CI: 0.60-2.44) respectively).…”
Section: (A) Exposure In Adulthoodmentioning
confidence: 99%